PENERAPAN MODEL PEMBELAJARAN PROBLEM-BASED LEARNING UNTUK MENINGKATKAN CARA BELAJAR YANG EFEKTIF DAN EFISIEN - Mardhiyantinengsih (Universitas Palangka Raya, 2022)
This research is a Guidance and Counseling Action Research which aims to improve the effective and efficient way of learning for students by applying the Problem Based Learning Model. This research was conducted in a participatory manner for one cycle. Data collection using observation sheets, and field notes. The data analysis used is qualitative analysis. This study shows that students experience an increase in learning effectively and efficiently in cycle I. The increase in student learning occurs because in learning by applying the Problem Based Learning model students are active by discussing each group that has been divided to observe problems in adolescent development that occur in environment around students, students are trained to analyze and solve problems from the results of the videos that have been played. Then present the results of the discussion in front of the class. This shows that the Problem Based Learning learning model can improve students' effective and efficient learning methods